HOST UTILIZATION PATTERNS IN THE PARASITE GUILD OF THE GALL MIDGE, ASPHONDYLIA RUDBECKIAECONSPICUA - Plakidas, John D. (My University, 1990)
I hypothesized that as a result of differences in the ovipositor lengths of the wasps Rileya americana and Torymus spp. depth partitioning of their host, the gall midge Asphondylia rudbeckiaeconspicua, would result in summer galls. Wasp inhabitants of summer galls formed by A. rudbeckiaeconspicua occupied elliptical chambers approximately 2.5 mm in width and 4.5 mm in length. The wasps that parasitized A. rudbeckiaeconspicua were equipped with an ovipositor used to penetrate the plant tissue of the gall and deposit an egg in or on the host. Ovipositor length measurements revealed that: 1. an unidentified Torymus sp. and T. advenus had ovipositors of the same length, 2. R. americana had a significantly shorter ovipositor than Torymus spp. Adult emergence dates were recorded for all species from both spring and summer galls. Results revealed that R. americana females emerged significantly later than A. rudbeckiaeconspicua females from both spring and summer galls. Similarly, Torymus spp. females emerged from summer galls later than did female A. rudbeckiaeconspicua. Depth measurements of A. rudbeckiaeconspicua summer gall chambers occupied by R. americana and Torymus spp. revealed that: 1. gall chambers were distributed over a range of depths from 2.0 to 20.0 mm; 2. Torymus sp. and T. advenus occupied gall chambers of the same range of depths; 3. R. americana occupied gall chambers deeper than did Torymus spp.; 4. Pianka's index of overlap revealed that overlap occurred between R. americana and Torymus spp. primarily in gall chambers from 3 to 7.0 mm, whereas no significant overlap occurred between R._ americana and Torymus spp.in chambers deeper than 7.0 mm. Depth partitioning of A. rudbeckiaeconspicua by R. americana and Torymus spp. did not occur. Time partitioning in the sequence of oviposition between R. americana and Torymus spp. in relation to gall development is believed to be responsible for their subsequent depth of occurrence. Therefor, the depth partitioning hypothesis was found to be an inappropriate model for describing the depth relationship for R. americana and Torymus spp. in A. rudbeckiaeconspicua summer gall chambers.